Optimasi Kapasitas Produksi untuk Mendapatkan Keuntungan Maksimum dengan Linear Programming - Ellysa Nursanti; Rina Intan Purnama; Ida Bagus Suardika (Performa: Media Ilmiah Teknik Industri, 2015)
Higher demand requires company to optimize its production capacity. Optimization of production capacity can be done in many ways, such as making optimal scheduling of working hours, adding overtime, adding labor or adding machine. However, due to limited capital these demand often be ignored. If the problem continues, the company would have lost sales, which affect to the company's profits. For that, it needs to be optimized by considering the company's production capacity of existing human resources. In this research, the production capacity optimization is done by determining daily working hours, using linear programming methods. This model has the objective function to maximize profit. The model considers gross revenue, production costs, and lost sales simultaneously to obtain the optimum working hours per day. As the result, it is obtained that the model is a maximum function. Increasing production capacity means increasing profit. But, the production capacity only be increased up to it’s maximum level. Over the level, the profit becomes less and continuing to decrease. Numerical example is also given to show the model characteristic and its sensitivity analysis.